Firm-specific characteristics and environmental disclosure: A study of selected listed companies in Sri Lanka - Silva, M.A.G.A.D. (University of Jaffna, 2020)
The environment is a valuable gift for us received by nature. However, most of the activities done by people and the organizations cause damage to the environment and eventually, sustainability. To be more specific, organizations damper the environment due to their industrial works. Therefore, there is an emerging need to protect the environment. Furthermore, the concern for environmental protection is becoming high among the corporate bodies, and in the present era, organizations tend to disclose more on environmental-related activities. So, this study aims to investigate factors that determine the Environmental Disclosures (ED) and, more specifically, the relationship between Firm Characteristics and the extent of the ED of Sri Lankan listed companies. ED was measured in terms of content analysis, and environmental disclosure is quantified by referring to the guidelines (G3) laid down in Global Reporting Initiatives (GRI). Data was gathered over a period of five years from 2013- 2017from top 25 companies listed on the Colombo Stock Exchange (CSE), Sri Lanka. Company characteristics as proxied by size, profitability, and age are considered explanatory variables that may influence the extent of sampled companies' environmental disclosures. The content analysis results showed that ED within annual reports are at a moderate level, and most of the companies have disclosed ED within the annual reports. The pooled regression analysis results indicate that company size and profitability are positively related to the extent of Environmental Disclosure, whereas company age has no statistically significant relationship with the extent of disclosure.
Keywords: content analysis; environmental disclosures; firm characteristics and GRI